How To Always Get The Jammie Dodger: Developing the Online Management Development Facilitator - Holmes, Matthew; Hoyle, Robin; Marder, Lucy; Tate, Martin (Proceedings of the International Conference on Networked Learning, 2002)
This workshop is designed to give conference participants a genuine experience of the challenges facing the developing e-tutor. The motivation for the workshop is our wish to share with others working in the field some of the experiences we have had in developing capable e-tutors for a single-company accredited learning programme delivered in partnership with a University business school.